Application of Multi-Age Differentiated Instruction Based on a Combination of Concrete 3D Shape Model Making and PhET Simulation by Elementary School Students - Ana Uzla BatuBara; Mhd Hanafi; Zainab Batubara (Jurnal Pengabdian Masyarakat Variasi, 2026)
Imbalance in learning readiness levels and age diversity (multi-age) in elementary schools often pose challenges in teaching abstract 3D geometry concepts. This Community Service Project (PkM) aimed to implement multi-age differentiated instruction through a combination of concrete media (sticks and modeling clay) and PhET digital simulations to enhance students' understanding of 3D geometric shapes. The project involved 4th and 5th-grade students grouped heterogeneously, a team of lecturers as supervisors and evaluators, and university students as facilitating mentors. The implementation method adopted a Blended Experiential Learning framework consisting of four stages: initial diagnostic mapping, student mentor training, differentiated learning intervention (introduction, concrete and digital exploration stations, and student product presentations), and evaluation. The results indicated a significant improvement in students' conceptual understanding of geometry, evidenced by an increase in the mean student score from 47.17 (pre-test) to 85.16 (post-test), with an average N-gain score of 0.72 (high category). The synergy of blended media successfully facilitated students' cognitive transition from the concrete operational stage to visual-abstract comprehension, while multi-age grouping triggered effective peer tutoring. The active participation rate reached 92%, proving that this approach is adaptive and inclusive in accommodating the heterogeneity of elementary school students.